Evaluasi Pertumbuhan Asystasia gangetica (L.) T. Anderson Sebagai Tanaman Penutup Tanah di Perkebunan Kelapa Sawit Menghasilkan pada Jarak Tanam dan Jenis Setek Batang Berbeda - Yenni Asbur; Yayuk Purwaningrum; Murni Sari Rahayu; Dedi Kusbiantoro; Khairunnisyah Khairunnisyah (Pusat Penelitian Kelapa Sawit, 2022)
Asystasia gangetica (L.) T. Anderson is an invasive weed that must be controlled in oil palm plantations. However, the results showed that previously in Semanjung Malaysia A. gangetica was used as a cover crop in oil palm plantations. The purpose of this study was to determine the best spacing and stem cuttings that produced the best growth of A. gangetica as a cover cover crop in mature oil palm plantations. The study used a factorial randomized block design with six replications at a plot size of 2 m x 2 m with plant spacing (10 cm x 10 cm, 20 cm x 20 cm, and 40 cm x 40 cm) and stem cuttings (top cuttings, middle cuttings, and bottom cuttings) as treatment. The results showed that the plant spacing of 10cm x 10cm is the optimum plant spacing for the growth of A. gangetica as cover crop as indicated by higher survived plant percentage and faster soil coverage than the spacing of 20cm x 20cm and 40cm x 40cm. Top cuttings are the best way to multiply A. gangetica to get optimal growth as cover crop.